Effect of water stress on physiological traits of sunflower (Helianthus annuus L.) restorer lines: EFFECT OF WATER STRESS ON PHYSIOLOGICAL TRAITS OF SUNFLOWER RESTORER LINES - LAKSHMI PRAYAGA; B YASASWINI CHOWDARY; S NARENDER REDDY; K B ESHWAR; H P MEENA; B SRIKANTH (Journal of Oilseeds Research, 2021)
A field experiment was conducted during rabi, 2018 to evaluate the performance of eight sunflower restorer lines viz., RGP 21-P6, RGP 32-P1, RGP 33-P5, RGP 50-P1, RGP 60-P2, RGP 61-P1, RGP 61-P2 and RGP 95-P1 for physiological traits under water stress conditions in a split-plot design with three replications. Water stress was imposed in stress plots from flowering to harvest. Results indicated that the traits, leaf area index (LAI), total drymatter (TDM), proline accumulation, and crop growth rate (CGR) were more sensitive to moisture stress with above 30% reduction. Whereas, SPAD chlorophyll meter readings (SCMR) was less sensitive with less than 10% reduction due to water stress. Significant decrease and variation was observed among the restorer lines for LAI, SCMR, TDM, relative water content (RWC) andCGR, whereas leaftemperature and proline concentration increased due to water stress. Restorer lines RGP 21-P6, RGP 61-P1, RGP-61-P2, and RGP 95-P1 recorded superiority inLAI, CGR, TDM and leaf temperature among the physiological traits studied even under water stress.